1960
DOI: 10.1021/jo01080a004
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Mixed Carboxylic-Carbonic Anhydrides1a

Abstract: CARBOXYLIC-CARBONIC ANHYDRIDES 1703 is 75°; 20 these authors also reported its conversion to cinnamic acid by boiling hydrochloric acid, a result which we duplicated. A sample of the acid (0.6 g.) was heated to boiling with 25 cc. 6.0N hydrochloric acid and gave, on cooling, crystalline cinnamic acid (0.45 g.), melting point and mixed melting point with authentic cinnamic acid, 130-132°, Oxidation of 2-(8-styryl)-4-methyl-l,3-dioxolane (Via) with peracetic acid catalyzed hy sulfuric acid. To 76 g. (0.4 mole) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Moreover, Tarbell and Longosz [46b] have demonstrated that the purely thermal reaction of the mixed anhydride of benzoic and (R)-2-octylcarbonic acid takes place with complete retention of configuration with respect to the formed (oct-2-yl) benzoate as well as di(oct-2-yl) carbonate that was built as minor product. The observed retention of configuration excludes any intramolecular cyclic transition state for ester formation as has been proposed [44].…”
Section: Scheme 10supporting
confidence: 64%
See 2 more Smart Citations
“…Moreover, Tarbell and Longosz [46b] have demonstrated that the purely thermal reaction of the mixed anhydride of benzoic and (R)-2-octylcarbonic acid takes place with complete retention of configuration with respect to the formed (oct-2-yl) benzoate as well as di(oct-2-yl) carbonate that was built as minor product. The observed retention of configuration excludes any intramolecular cyclic transition state for ester formation as has been proposed [44].…”
Section: Scheme 10supporting
confidence: 64%
“…[42]) 10 ), in particular with those of Windholz [44] and Green [45], who found that mixed anhydrides of type 9, composed of carboxylic acids with electron-withdrawing groups, such as in cyano-, (p-nitrophenyl)-or trifluoroacetic acid, and alkylcarbonic acids give, on gentle heating, a nearly quantitative evolution of CO 2 with formation of the corresponding alkyl carboxylates in 80 ± 95% yield. On the other hand, steric crowding in the a-position of the carboxylic part, e.g., diphenylacetic acid, favors formation of the symmetric carboxylic anhydrides, and the corresponding esters are the minor part of the reaction mixtures [44].…”
Section: Scheme 10mentioning
confidence: 98%
See 1 more Smart Citation
“…The ions I11 and IV Xr, Ar Ar A r formed b~-route n can recombine to form the carbosylic-carbonic anh~~clricle (V): 1,cSfler (3) has alreac1~-obtained ail anh~,dricle of this type by rearrangement of p-1uethox~--plnitrobenzo~ 1 peroxide in thionyl cl~loricle. Benzoic-pl~en~~lcarbonic anhydride (V; .Ar = Ph) was reported by Windholz (6) to decoinpose to give a 10yo yield of phenyl benzoate (equation [3]) and yields of benzoic anhydride and diphenyl carbonate (equation [1] %yo of ethyl benzoate and 5070 of benzoic anhydride; however, in the presence of boron trifluoride etherate, decolnposition taltes place a t room temperature to give ethyl benzoate alnlost exclusively (6). Similarly we have found benzoic-ethylcarbonic anhydride in benzene deconlposes a t rooln temperature in the presence of alulninun~ chloride to give a 48% yield of ethyl benzoate and 14% yield of benzoic acid (presumably from benzoic anhydride).…”
mentioning
confidence: 91%
“…Similarly we have found benzoic-ethylcarbonic anhydride in benzene deconlposes a t rooln temperature in the presence of alulninun~ chloride to give a 48% yield of ethyl benzoate and 14% yield of benzoic acid (presumably from benzoic anhydride). The mechanism for the catalyzed decomposition of benzoic-phenylcarbonic anhydride (V; Ar = Ph) shown in Scheme I is suggested by the fact that the uncatalyzecl decomposition is greatly facilitated by electron-withdrawi~lg groups in the acyl portion of the anhydride (6)(7)(8)(9).…”
mentioning
confidence: 99%